Is red blood cell distribution width an indicator of prognosis and mortality in respiratory intensive care unit? - Eraslan Doğanay, Güler; Cırık, Mustafa Özgür (The European Research Journal, 2021)
Objectives: The range of variation of erythrocytes measured as Red blood cell distribution width (RDW). Mortality indicators in patients in intensive care depend on variation of physiological variables. High RDW rates have been commonly associated with heart disease, pulmonary embolism and pulmonary hypertension, peripheral artery disease, heart failure, liver disease and infectious diseases. We aimed in this study to determine the effect of RDW on prognosis and mortality in Chronic Obstructive Pulmonary Disease (COPD) patients in intensive care unit (ICU). Methods: The cases who are treated for COPD in ICU between January 1, 2018 and December 31, 2019 reviewed. Demographic data, Charlson Comorbidite Index (CCI), Acute Physiology and Chronic Health Evaluation II (APACHE II), Sequential Organ Failure Assessment (SOFA) scores, procalcitonin, white blood cell, RDW, C-reactive protein, duration of mechanical ventilation, inotrope requirement, length of stay ICU, and 30-day mortality reviewed. Results: Total number of 369 cases are included into the study and divided in two groups according to their RDW values (High RDW and normal RDW group). High RDW group had longer length of stay in ICU and hospital, mechanical ventilation duration, higher APACHE II, CCI, SOFA, white blood cell and procalcitonin values and lower C-reactive protein compared to normal RDW group. First outcome was hospital 30-day mortality in ICU. The age, RDW, inotrope use, MV duration, LOS H, APACHE II, CCI, SOFA, procalcitonin, CRP, HGB and HCT levels were found to be higher in patients with mortality compared those without. With the sensitivity value of 70.9% and the specificity of 47.7%, RDW the cut off value was found to be 16.5. Conclusions: The risk of 30-day mortality, length of stay ICU and hospital and mechanical ventilation duration was higher in COPD patients with high RDW levels.